DOMESTIC AIR TRANSPORT REGULATIONS IN INDONESIA - Kemis Martono; Sandriana Marina; Aditya Wardana (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2016)
The purpose of this study is to explore the implementation of provisions of the domestic air transport regulations provided in the 2009 Civil Aviation Act. The method is a library research that study the scheduled air transportation including the requirement of the establishment of airlines; capital of air transport business entities, aircraft ownership and operation requirements, share holder composition, bank guarantee requirements, aviation human resources; tarif’s regulations including passenger’s tariff, passengers’ protection, best practices; non-scheduled air transportation; general aviation and air transportation pioneer has been fully implemented and compliances with the airlines. It is concluded that the provision of air transport regulation provided in the Civil Aviation Act of 2009 has been fully implemented and compliances with the airlines in Indonesia.